A crux interpretum in Jas 4,5 = Crux Interpretum v Jak 4,5 - Mareček, Petr (Edinost in dialog, 2020)
Verse Jas 4,5 poses two problems for exegetes. On the one hand, it is not easy to identify the apparent quotation from Scripture, and on the other hand, it is difficult to de-termine the meaning of this verse as a whole, as well as each statement in it. This text begins with a rhetorical question (»Or do you think it doesn’t make sense what Scripture says?«, Jas 4,5a) and is followed by a statement (»He [God] jealously longs for the spirit which [God] dwelt in us«, Jas 4,5b). The statement Jas 4,5b, which is presented as a biblical quote, is not found in the Old Testament or in the surviving unbiblical writings as a literal quote. It is not entirely possible to exclude the option that James cites an unknown work in Jas 4,5b, but it is more likely that he created a biblical quote from various elements of Scripture on the subject of God’s jealousy, which is linked to the idea of Israel’s chosen people as the bride of their God.